Application of the bifurcation method to the modified Boussinesq equation - Shaoyong Li (Electronic Journal of Qualitative Theory of Differential Equations, 2014)
In this paper, we investigate the modified Boussinesq equation $$u_{tt}- u_{xx}-ε u_{xxxx}-3(u^2)_{xx}+3(u^2u_x)_{x}=0.$$ Firstly, we give a property of the solutions of the equation, that is, if $1+u(x, t)$ is a solution, so is $1-u(x, t)$. Secondly, by using the bifurcation method of dynamical systems we obtain some explicit expressions of solutions for the equation, which include kink-shaped solutions, blow-up solutions, periodic blow-up solutions and solitary wave solutions. Some previous results are extended.